The Influence Of Brand Image And Perceived Quality On Muslim Millennials' Purchase Interest In Local Fashion Brand Products - Shiddieq, Muhammad Biagi Hafizh; Juliana, Juliana; Utami, Suci Aprilliani; Marlina, Ropi (Iqtisad: Journal of Islamic Economic and Civilization, 2025)
Around 60% of consumers dominated by Muslim millennials still pursue imported fashion brands because they are recognized as having better quality and prestige, even though they know that the price of local fashion products is more affordable. The purpose of this study is to determine the influence of brand imageand perceived quality on the purchase interest of Muslim millennials in Islamic economics study program students at State Universities in Bandung City. The method used in this study is the causality method with a quantitative approach and hypothesis testing design. The study was conducted on students of Islamic economics study programs at State Universities in Bandung City including UPI, UIN, and UNPAD. The results of the study showed that brand image and perceived quality influenced the purchase interest of Islamic economics students in fashion products in Bandung City. The researcher hopes that the results of this study can provide benefits for various parties, especially local business actors, so that they can pay more attention to brand image and perceived quality to increase purchase interest in local fashion products in Bandung City.